Model Pengembangan Kampung Wisata Blangkon di Surakarta Berbasis Konsep Kearifan Lokal - Triratma, Bambang; Winarto, Yosafat; Yuliani, Sri (ARSITEKTURA, 2019)
Blangkon is a product of local wisdom that has high heritage value as a part of a Javanese traditional costume since the kingdom period of Surakarta. To increase durability and sustainability the blangkon home industries have to adapt to trend development. The research aims to build a model of tourism village based on local wisdom. The method of phenomenology observation was applied to find aspects that have a good opportunity to be integrated directly and indirectly with the product and production of blangkon. The fusion of those two aspects became a part of tourism activities in Surakarta and The Province of Central Java. The result of research leads to some important conclusions. The product and production of blangkon have to be integrated harmoniously with some other aspects and activities especially those based on local wisdom in order to build and to save the blangkon becoming an important heritage matter and commodity. Finally, the model of tourism village based on local wisdom has to be built by involving the local community to guarantee they are going to get a better life in the future. It has three main parts, namely components, management and sustainability of the model.